Supramolecular Polymer Intertwined Free-Standing Bifunctional Membrane Catalysts for All-Temperature Flexible Zn–Air Batteries - Wagh, Nayantara K.; Shinde, Sambhaji S.; Lee, Chi Ho; Kim, Sung‑Hae; Kim, Dong‑Hyung; Um, Han‑Don; Lee, Sang Uck; Lee, Jung‑Ho (Nano-Micro Letters, 2022)
Rational construction of flexible free-standing electrocatalysts featuring long-lasting durability, high efficiency, and wide temperature tolerance under harsh practical operations are fundamentally significant for commercial zinc–air batteries. Here, 3D flexible free-standing bifunctional membrane electrocatalysts composed of covalently cross-linked supramolecular polymer networks with nitrogen-deficient carbon nitride nanotubes are fabricated (referred to as PEMAC@NDCN) by a facile self-templated approach. PEMAC@NDCN demonstrates the lowest reversible oxygen bifunctional activity of 0.61 V with exceptional long-lasting durability, which outperforms those of commercial Pt/C and RuO2. Theoretical calculations and control experiments reveal the boosted electron transfer, electrolyte mass/ion transports, and abundant active surface site preferences. Moreover, the constructed alkaline Zn–air battery with PEMAC@NDCN air–cathode reveals superb power density, capacity, and discharge–charge cycling stability (over 2160 cycles) compared to the reference Pt/C + RuO2. Solid-state Zn–air batteries enable a high power density of 211 mW cm−2, energy density of 1056 Wh kg−1, stable charge–discharge cycling of 2580 cycles for 50 mA cm−2, and wide temperature tolerance from − 40 to 70 °C with retention of 86% capacity compared to room-temperature counterparts, illustrating prospects over harsh operations. Highlights: 1 Rational design of 3D flexible free-standing membrane catalysts with protonation between supramolecular polymers and nitrogen-deficient carbon nitride nanotubes frameworks via facile bottom-up self-conversion approach. 2 PEMAC@NDCN demonstrates the lowest reversible oxygen bifunctional activity of 0.61 V with exceptional long-lasting durability, surpassing the commercial and reported champion oxygen catalysts. 3 Engineering catalytically active cathode materials enabled all-temperature flexible Zn–air batteries with high electrochemical and mechanical performances (temperature of − 40 to 70 °C) under harsh operations.